Statystyczna ewidencja spraw o odszkodowania z tytułu odpowiedzialności cywilnej podmiotów leczniczych w Polsce - Korytkowska, Daria (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The article analyses damage claims for medical malpractice in Poland. Thearticle describes types of responsibility for medical malpractice. Although availabledata have been analyzed, the evidence suggests that official statistical dataunderestimates the number of claims. The reason for such underestimation layswith existing barriers that discourage patients from claiming the damages. Eventhough new methods of claiming damages were introduced, the barriers remainin place. Therefore the author proposes introduction of monitoring of cases heldin courts in order to improve the value of statistical data which would lead to moreefficient investigation of medical malpractice claims by the existing VoivodeshipCommittees.